Quantitative Assessment of Serum NV-F Virus DNA Concentrations in Samples from Patients Coinfected with Hepatitis B or C Virus - Hsu, Chao-Wei (American Society for Microbiology, 2006)
A novel hepatotropic virus, named NV-F virus, was recently identified. The clinical information for this virus is still scarce. Using PCR assay, NV-F viral DNA (NV-F-DNA) was detected in 12 of 50 (24%) hepatitis C virus (HCV)-infected patients (HCV-coinfected [HCVCI] group), 34 of 250 (13.6%) hepatitis B virus (HBV)-infected patients (HBV-coinfected [HBVCI] group), and 28 of 100 (28%) non-A-to-E (NAE) hepatitis patients. Basic clinical parameters were not significantly different among the three groups. By use of a PCR-based quantitative assay, the NV-F-DNA concentration was found to be above the detection limit (1.2 × 10(5) copies/ml) in 12/12 (100%) HCVCI patients, 14/34 (41.2%) HBVCI patients, and 4/28 (14.3%) NAE patients. The median serum NV-F-DNA concentration was 9.3 × 10(5) copies/ml in HCVCI patients, but it was below the detection limit in HBVCI and NAE patients (P values were 0.0045 and 0.0001, respectively). Stepwise multiple regression analysis identified the presence of anti-HCV as an independent factor for NV-F-DNA concentrations (β = 6.2 × 10(9); P = 0.0245). In HBVCI patients, the NV-F-DNA concentration was inversely correlated with the HBV DNA concentration. The median NV-F-DNA concentration was below the detection limit in patients with HBV DNA concentrations above 1.4 × 10(5) copies/ml, but it was 1.58 × 10(6) copies/ml in patients with HBV DNA concentrations below 1.4 × 10(5) copies/ml (P = 0.030). In conclusion, NV-F-DNA concentrations were higher in HCVCI patients. A reciprocal relationship was found between NV-F-DNA and HBV DNA concentrations in HBVCI patients, indicating the presence of viral interference between these two DNA viruses.